Clinically significant hypermagnesemia in a healthy individual: a rare entity - Manjavkar, Smita; Kharaje, Jayashree; Malgaonkar, Aniruddha (International Journal of Research in Medical Sciences, 2016)
Clinically significant hypermagnesemia is rare in individuals with normal renal functions. Its cause is often iatrogenic. In this case a young married female had significant hypermagnesemia with normal renal function. The clinical spectrum of hypermagnesemia can range from subtle neurological signs to major life threatening shock, dysarrthymias and coma. The patient was treated with intravenous hydration, Ca-gluconate and furosemide. Patient responded to the treatment and her serum magnesium levels decreased to 4.00mEq/l.